2007
DOI: 10.1128/jvi.00844-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Fusion Protein Vaccines That Are Immunogenic and Protective in Cotton Rats

Abstract: Human metapneumovirus (hMPV) is a recently described paramyxovirus that is a major cause of upper and lower respiratory infection in children and adults worldwide. A safe and effective vaccine could decrease the burden of disease associated with this novel pathogen. We previously reported the development of the cotton rat model of hMPV infection and pathogenesis (J. V. Williams et al., J. Virol. 79:10944-10951, 2005). We report here the immunogenicity of an hMPV fusion (F) protein in this model. We constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 58 publications
(74 reference statements)
3
85
0
Order By: Relevance
“…At this time we have not developed a firm opinion as to the mechanism of vaccine induced enhancement with members of this virus family, but can conclude from these findings that inactivated hMPV vaccine candidates should be thoroughly screened for safety. Recent publication by Cseke et al [5] shows no vaccine enhancement when cotton rats are immunized with either DNA plasmids expressing F-protein of hMPV or adjuvanted, soluble hMPV F protein lacking the transmembrane domain then challenged. This may suggest that the native form of F protein may not be involved in the mechanism of vaccine enhancement for hMPV.…”
Section: Discussionmentioning
confidence: 99%
“…At this time we have not developed a firm opinion as to the mechanism of vaccine induced enhancement with members of this virus family, but can conclude from these findings that inactivated hMPV vaccine candidates should be thoroughly screened for safety. Recent publication by Cseke et al [5] shows no vaccine enhancement when cotton rats are immunized with either DNA plasmids expressing F-protein of hMPV or adjuvanted, soluble hMPV F protein lacking the transmembrane domain then challenged. This may suggest that the native form of F protein may not be involved in the mechanism of vaccine enhancement for hMPV.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal anti-hMPV antibody was generated by infecting guinea pigs twice intranasally with 10 5 pfu of sucrose-gradient-purified hMPV. This anti-hMPV antibody has low nonspecific background, does not cross-react with other viruses by immunofluorescence or immunoblotting, and detects recombinant hMPV F protein with high sensitivity (8,56). Function-blocking human integrin-specific mAbs MAB2021Z (␣v; clone AV1), MAB1957Z (␤3; clone 25E11), and MAB1976Z (␣v␤3; clone LM609) were purchased from Chemicon.…”
Section: Methodsmentioning
confidence: 99%
“…Two of these are membrane-anchored glycoproteins, the fusion (F) and attachment (G) proteins. Studies of mutant viruses and recombinant proteins show that F is the major protective antigen (8)(9)(10). The hMPV F protein is similar to other paramyxovirus fusion proteins and incorporates homologous regions that likely have homologous functions (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since other studies have already demonstrated the capacity of postfusion hMPV F to induce protective immune responses in cotton rats (Cseke et al , 2007), hamsters (Herfst et al , 2007), mice (Aerts et al , 2015), and macaques (Herfst et al , 2008), the chimeric proteins could have the advantage over the epitope scaffolding approach in that they would confer protection simultaneously against more than one virus. This possibility however needs to be tested directly in perhaps more permissive animal models such as cotton rats where protection in the upper and lower respiratory tract against hRSV and hMPV could be assessed.…”
Section: Discussionmentioning
confidence: 99%